Cyclic stretch-mediated release of vascular endothelial growth factor by vascular smooth muscle cells : a role in improved vascular graft patency - Smith, James Douglas (Division of Cardiology, 2017)
In the light of studies which show the upregulation of VEGF in contractile cells subjected to cyclic stretch and the profound effects which cyclic stretch has been shown to have on the release of other cytokines by SMC, this study investigates the role which cyclic stretch might play in VEGF expression by SMC in a compliant environment. Furthermore, following observations of receptor phosphorylation in response to cyclic stretch in vascular cells, the effect of cyclic strain on the KDR-mediated endothelial response to locally-released VEGF was also investigated. Low passage number bovine aortic SMC and EC were plated on collagen-coated elastomer plates and subjected to 10% repetitive strain at 1 Hz. The mRNA expression of VEGF in SMC and the phosphorylation of KDR on EC were determined by northern blotting and western blotting respectively. The biological activity on EC and levels of VEGF secreted into the medium by SMC under cyclic stretch were investigated using a migration assay and ELISA respectively. Cyclic stretch was found to cause a 3.3 (±1.5 p < 0.005) fold increase in VEGF mRNA levels over unstretched controls at 4 hours. This biomechanically-induced expression was found to drop slightly by 24 hours and to be approximately equivalent to expression induced by the cytokine bFGF over the same time course. These results correlated with an increase in VEGF levels in media from stretched SMC capable of inducing migration of EC by 1.6 fold although additional EC chemotactic factors appear to be released by stretch. Furthermore, although the levels of KDR remained constant under cyclic stretch, average KDR phosphorylation was found to increase weakly over time due to cyclic stretch. These results show that cyclic stretch affects the VEGF communication between SMC and EC at both the level of VEGF expression by SMC and at the level of VEGF recognition by the KDR receptor on EC. It is possible that through the nitric oxide (NO) pathway, VEGF release may alleviate abnormally high levels of cyclic strain. It is hoped that a better understanding of the role of VEGF communication between stretched SMC and EC will enable the design of a graft in which the level of compliance encourages SMC to maintain a functional endothelium. Following this it is hoped that the low levels of SMC and pericytes invading the graft, pacified by endothelial cell mediation, will not result in intimal hyperplasia but rather play a role in microvessel maintenance and more complete healing.